Demo: A FSM Approach to Web Collaboration - Gadea, Cristian; Ionescu, Bogdan; Ionescu, Dan (Proceedings of the International Conference on Distributed Computing Systems, 2021)
Operational Transformation (OT) algorithms, at the heart of web-based collaboration, have been studied since the late 1980s and remain a hot research subject. Centralized versions of OT algorithms that can be implemented on top of cloud-based serverless platforms are still unexplored. This poster introduces a Control Loop view of OT algorithms that are modeled by a series of Finite State Automata (FSAs) embedded in a serverless system architecture. A series of nested Finite State Machines (FSMs) dynamically control the co-editing processes. The proposed platform was simulated to demonstrate the correctness of the OT algorithms. Results obtained from the simulation are presented and an interactive demonstration is given.